Exploring China's religious sites - Hong, Zhaohui, 1959- author. Link
1 online resource
Keywords: "This book employs cutting-edge digital and spatial methodologies to tackle the critical issue of religious site scarcity across China for five major religions: Protestantism, Catholicism, Buddhism, Taoism, and Islam, spanning the period from 1911 to 2004. Drawing from Chinese government datasets and Geographic Information Systems (GIS), this comprehensive work presents official information concerning religious sites and pinpoints specific cities facing shortages in such sites. The book also offers an in-depth analysis of religious sites, delving into their historical context and evolving significance within China, shedding light on the unique challenges and opportunities each religion faces. Uncovering spatial patterns and relationships that shed new light on the distribution of religious sites and valuable insights into the evolution of Chinese religious practices since 1911, this groundbreaking book will be an excellent resource for students and scholars of modern China and religious studies, as well as digital and spatial humanities"--